Mapping quantitative trait loci for cold tolerance in rice at seedling stage (Bangladesh Journal of Botany, 2019)
Rice plants are sensitive to cold stress at various growth stages starting from germination to maturity. Exploitation of cold tolerance for the development of cold tolerant varieties may help in saving crop loss or cost of production in the cold prone environment. Introgression of quantitative trait loci (QTLs) conferring cold tolerance in the elite variety may be the most effective and sustainable approach to address this issue. A F2:3 mapping population of a cross between a cold susceptible variety (BR1) and a cold tolerant variety (BR18) was used to map QTLs for cold tolerance at seedling stage. Three significant QTLs on chromosomes 1, 3 and 12 associated with cold tolerance were mapped between the markers intervals of RM220-RM10829, RM546-RM7 and RM27877-RM463, respectively at a threshold LOD of 4.3 through composite interval mapping. Phenotypic contributions of these QTLs were 50.7, 39 and 52.7%, respectively. Marker information of such a large effect QTL could be used in the breeding program after necessary validation to develop cold tolerant high yielding rice varieties.